Überzeugungen zum Technologieeinsatz im Mathematikunterricht: Entwicklung eines Messinstruments für Lehramtsstudierende und Lehrkräfte (mathematica didactica, 2021)
Beliefs referring to teaching and learning mathematics with technology play an important role when teachers are integrating technology into their classroom. However, instruments to measure those beliefs in detail are not available yet. In this article we are contributing a detailed inventory to measure technology-related beliefs of in- and pre-service teachers. The questionnaire is analyzed with 246 pre- and 199 in-service teachers using confirmatory factor analysis. It is found, that beliefs of in-service teachers can be measured in more detail than those of pre-service teachers.